The construction and evaluation of secretory expression engineering bacteria for the trans-Cry3Aa-T-HasA fusion protein against the Monochamus alternatus vector - Han, Xiaohong; Huang, Chenyan; Qi, Huan; Zhu, Yukun; Hu, Xinran; Wen, Yingxin; Long, Yirong; Xu, Lei; Zhang, Feiping (Frontiers in Cellular and Infection Microbiology, 2024)
Pine wood nematode disease is currently the most deadly forest disease in China, and the Monochamus alternatus is its primary vector. Controlling the M. alternatus is crucial for managing pine wood nematode disease. This study, based on the selected HasA (pGHKW4) secretory expression vector, used electroporation to combine the genetically modified high-toxicity toxin Cry3Aa-T with the entomopathogenic bacterium Yersinia entomophaga isolated from the gut of the M. alternatus. The SDS-PAGE and Western blotting techniques were employed to confirm the toxin protein’s secretion capability. The engineered bacteria’s genetic stability and effectiveness in controlling M. alternatus were assessed for their insecticidal activity. The results of the SDS-PAGE and Western blotting analyses indicate that the HasA system effectively expresses toxin protein secretion, demonstrates certain genetic stability, and exhibits high insecticidal activity against M. alternatus. This study constructed a highly toxic entomopathogenic engineered bacterial strain against M. alternatus larvae, which holds significant implications for controlling M. alternatus, laying the foundation for subsequent research and application of this strain.